Peran Kearifan Lokal Dalam Keberlanjutan Indigenous Tourism Baduy di Kabupaten Lebak Provinsi Banten - Anggoroningrum, Anis Ratih; Ingkadijaya, Rahmat; Rahman, Arief Faizal; Suprina, Rina; Nurbaeti, Nurbaeti (Jurnal Ilmiah Pariwisata, 2026)
This study is grounded in the importance of local wisdom in sustaining community-based tourism, particularly the practice of Indigenous Tourism in Kabupaten Lebak. The Suku Baduy community is widely recognized for consistently upholding pikukuh karuhun (ancestral customary law) as the foundation of social and ecological governance amid increasing tourist arrivals. This research aims to analyze the role of local wisdom in regulating tourist interactions, managing tourism impacts, and maintaining cultural and environmental sustainability.The study employs a qualitative approach using in-depth interviews, participatory observation, and documentation, analyzed through Interpretative Phenomenological Analysis (IPA). The findings reveal that customary values function as a social control mechanism through restricted access, rejection of modernization, and spirituality-based regulations. Tourism generates positive impacts, including the strengthening of the weaving-based creative economy and youth involvement, yet it also presents potential social and environmental pressures. The community applies selective adaptation to prevent excessive commodification and preserve cultural integrity. In conclusion, local wisdom serves as both an ethical foundation and a regulatory system ensuring the sustainability of Indigenous Tourism. The study recommends strengthening adat-based regulations, limiting visitor numbers, and implementing participatory monitoring systems to maintain economic, cultural, and environmental balance. Keywords: local wisdom, indigenous tourism, tourism sustainability, baduy community, customary governance